Decay of passively acquired measles antibody and its implications for vaccination - Rahman, ASM Matiur (Journal of Armed Forces Medical College, Bangladesh, 2009)
doi:10.3329/jafmc.v4i2.1818 JAFMC Bangladesh Vol.4(2) 2008 1